Influence of globalization and European integration processes on structural transformations in the Polish sugar industry - Niemczak, Marcin (Studies of the Industrial Geography Commission of the Polish Geographical Society, 2009)
The problem of economic transformation, and especially of structural transformations of industries in view of globalization and European integration becomes particularly significant. One of the most important effects of globalization, vital in modernization of economy, is restructuring of industry. This process requires precise recognition of the mechanisms of its functioning and identification and employment of these mechanisms in the process of adapting countries’ economies to the new, competitive conditions of the global economy.Such actions are indispensable to increase the competitiveness of products and services provided by enterprises.In the period of transformation, functioning of the Polish sugar industry depended not only on the current socio-economic conditions, but also on the influence of integration processes. As economic transformation, especially restructuring of enterprises, is strictly connected with great financial expenditure and with changes in the system of management, it had an effect on the course of transformations in the spatial structure of the Polish sugar industry